2016
DOI: 10.12659/msm.895573
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an Electronic Inspiratory Loading Device for Assessing Pulmonary Function in Post-Stroke Patients

Abstract: BackgroundThe purpose of this study was to examine the inter- and intra-rater reliability of an electronic inspiratory loading device for the assessment of pulmonary functions: maximum inspiratory pressure, peak inspiratory flow, and vital capacity.Material/MethodsSubjects were 50 patient volunteers in a rehabilitation hospital who had experienced their first episode of unilateral stroke with hemiparesis during the previous 6 months (26 men, 24 women; mean age [±SD], 55.96 [±12.81] years), with no use of medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Maximum inspiratory pressure (MIP), peak inspiratory flow (PIF), and VC were measured using an electronic inspiratory loading device (PowerBreathe K5, 2010, HaB International Ltd., UK) to determine inspiratory muscle function (Lee et al 2016). The device provides automatically processed information on MIP, PIF, and VC during loaded inspiration tasks (Fig.…”
Section: Respiratory Muscle Functionmentioning
confidence: 99%
“…Maximum inspiratory pressure (MIP), peak inspiratory flow (PIF), and VC were measured using an electronic inspiratory loading device (PowerBreathe K5, 2010, HaB International Ltd., UK) to determine inspiratory muscle function (Lee et al 2016). The device provides automatically processed information on MIP, PIF, and VC during loaded inspiration tasks (Fig.…”
Section: Respiratory Muscle Functionmentioning
confidence: 99%
“…Inadvertently, the S-Index has been confused with MIP to evaluate IMS. In this sense, Lee et al [2] (2016) revealed a high correlation coefficient of IMS intra-and inter-rater (0.986 and 0.984, respectively) in their study. They used the PowerBreathe K5 device to obtain those results; however, this device evaluates muscle strength at flow with an evaluation of the dynamic muscle contraction.…”
Section: Discussionmentioning
confidence: 60%
“…In theory, the S-Index is able to support the inspiratory muscle training (IMT) and is becoming popular due to its easy applicability and low cost, since the same device is able to provide IMS and inspiratory muscle resistance evaluation, in addition to the IMT. Besides that, comparing to the maximal inspiratory pressure (MIP), a better adaptation of individuals to the evaluation was reported, since a more functional maneuver is performed, mimicking the physiological contraction of the inspiratory muscles [2,3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal breathing patterns and trunk posture affect each other in stroke patients [34]. A study has confirmed that breathing training can significantly increase muscle strength and trunk coordination in stroke patients with hemiplegia and also improve respiratory function [35,36]. It has been reported that respiratory muscle strength training or complex breathing exercises can effectively improve the stability of the trunk posture of stroke patients [37], and it has been proven that resistance training of the thoracic cage can significantly improve respiratory function and the trunk control ability of stroke patients [38].…”
Section: Discussionmentioning
confidence: 95%